1998
DOI: 10.1016/s0005-2736(97)00181-8
|View full text |Cite
|
Sign up to set email alerts
|

Calcium-dependent conformation of E. coli α-haemolysin. Implications for the mechanism of membrane insertion and lysis

Abstract: Previous studies from this laboratory had shown that calcium ions were essential for the membrane lytic activity of E. coli alpha-haemolysin (HlyA), while zinc ions did not sustain such a lytic activity. The present data indicate that calcium-binding does not lead to major changes in the secondary structure, judging from circular dichroism spectra. However binding to Ca2+ exposes new hydrophobic residues at the protein surface, as indicated by the increased binding of the fluorescent probe aniline naphtholsulp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
51
0
5

Year Published

1998
1998
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(57 citation statements)
references
References 28 publications
1
51
0
5
Order By: Relevance
“…Our previous studies (66) have shown the difference between adsorption and insertion, and the requirement of a fluid (liquid disordered) bilayer for irreversible insertion. The more recent data by Bakás et al (84) demonstrate that Ca 2+ -binding is an additional requirement for irreversible insertion. This kind of insertion appears to be essential for the lytic process to go on (through yet unknown steps).…”
Section: More On the Role Of Divalent Cationsmentioning
confidence: 95%
See 4 more Smart Citations
“…Our previous studies (66) have shown the difference between adsorption and insertion, and the requirement of a fluid (liquid disordered) bilayer for irreversible insertion. The more recent data by Bakás et al (84) demonstrate that Ca 2+ -binding is an additional requirement for irreversible insertion. This kind of insertion appears to be essential for the lytic process to go on (through yet unknown steps).…”
Section: More On the Role Of Divalent Cationsmentioning
confidence: 95%
“…This suggests that Ca 2+ induces in the protein in solution a state such that the toxin becomes capable of producing membrane lysis. The same liposome-red blood cell competition assay for the irreversibility of Hly binding was applied by Bakás et al (84) in a new series of experiments to study the effects of Ca 2+ on toxin binding irreversibility and subsequent membrane damage, with the result that Ca 2+ facilitates the irreversible bilayer insertion of the protein. Looking in more detail into the HlyAcalcium system, the above authors observed that, even in the absence of lipid bilayers, Ca 2+ binding had significant effects on α-hemolysin.…”
Section: More On the Role Of Divalent Cationsmentioning
confidence: 99%
See 3 more Smart Citations